Platelet-activating factor. A potent chemotactic and chemokinetic factor for human eosinophils. - Wardlaw, A J (1986)
Platelet-activating factor (PAF-acether), an inflammatory mediator with a wide range of biological activities including neutrophil aggregation and chemotaxis, was studied for its effect on human eosinophil locomotion (chemotaxis and chemokinesis). Human eosinophils (25-95% purity) were obtained from donors with a variety of diseases associated with hypereosinophilia. PAF-acether elicited directional locomotion of eosinophils, in a time- and dose-dependent fashion, at concentrations from 10(-5) to 10(-8) M; lyso-PAF had minimal activity over the same dose range. Compared with PAF-acether, the eosinophil locomotory responsiveness of leukotriene B4 (LTB4), histamine, and the valyl- and alanyl-eosinophil chemotactic factor of anaphylaxis (ECF-A) tetrapeptides was negligible. Conversely, neutrophil responsiveness to PAF-acether (optimum 10(-6) M) was comparable in effect to LTB4 (optimum dose 10(-8) M). It was shown that PAF-acether elicited both chemotaxis and chemokinesis of eosinophils. Comparison of normal density and light density eosinophils revealed no qualitative difference in the response to PAF-acether and the other chemoattractants, although the light density cells seemed to demonstrate a greater degree of locomotion to PAF-acether and LTB4. Thus, PAF-acether appears to be a potent eosinophilotactic agent which may play a role in inflammatory reactions characterized by eosinophil infiltration.